Reducible chimeric polypeptide consisting of octa-d-arginine and tetra-l-histidine peptides as an efficient gene delivery vector - Wang, Xiaoyu (Int J Nanomedicine, 2015)
Cationic oligopeptide as a nonviral gene delivery vector has aroused much research interest recently, but its further application is limited by its low transfection efficiency. In the present study, we have created a high-efficiency gene vector by using octa-d-arginine and tetra-l-histidine to form a disulfide cross-linked chimeric polypeptide and used this vector to deliver the therapeutic gene tumor-necrosis-factor-related apoptosis-inducing ligand (TRAIL) to see whether the gene could be transferred and could exert antitumor effects in vitro and in vivo. The result showed that the newly designed vector was able to condense DNA into nanosized polyplexes effectively, thus facilitating its transmembrane transport, promoting its endosomal escape, and finally enabling degradation within the cell. Our study has demonstrated that this chimeric polypeptide is an effective gene carrier in cancer therapy.